Defective Interaction between von Willebrand Factor and Platelet Glycoprotein I b – A Familial Study of Peripheral Arterial Occlusive Disease - Kauhanen, Petteri; Beer, Jürg H; Lassila, Riitta (Thrombosis and Haemostasis, 1997)
Hemostatic variables and platelet function were assessed as a part of a genetic study in 15 patients with symptomatic peripheral arterial occlusive disease (PAOD) and 15 healthy siblings from ten families. D-dimer, a degradation product of cross-linked fibrin, was increased in the PAOD group (mean ± SD) (448 ± 177 vs. 333 ± 121 ng/ml, p <0.05). Ristocetin-induced maximal platelet aggregation (RIPA) was reduced in the PAOD group in response to both a higher (0.75 mg/ml) (67 ± 28 vs. 87 ± 14%, p = 0.02) and a lower (0.55 or 0.60 mg/ml) (33 ± 21 vs. 59 ± 32%, p = 0.02) concentration of ristocetin. Accordingly, the rate of primary aggregation was smaller, and a larger threshold concentration of ristocetin was needed to cause aggregation. However, ristocetin cofactor activity, von Willebrand factor (vWF) antigen and its multimer distribution, plasma glycocalicin, platelet glycoprotein lb content and the binding of vWF to frozen and thawed washed platelets were equal in both groups. Thus, the observed reduced RIPA in patients with PAOD is likely to reflect a down-regulation or blunted binding affinity in the platelet surface glycoprotein Ib.